Students’ attitudes in the Republic of Srpska towards trap music: From dominant narratives to current music preferences - Vukojević, Bojana (Sociološki pregled, 2024)
Historically speaking, different musical genres have periodically been a reason and a tool in the labelling of certain social groups, and recently, similar cautionary narratives have been found in trap music as well. They range from concern for young people’s tastes, values and understanding to a moral panic that requires the regulation of public policies and the response of political actors. This observation of musical preferences is the result of a long-term understanding of cultural consumption through Pierre Bourdieu’s theory of homology, where tastes appear as indicators of the status in society, that is, they indicate social hierarchies in which those who consume elite culture are at the top, while mass culture is reserved for the lower classes of society. As an alternative, Richard Peterson’s theory of cultural omnivores and univores stands out in social sciences, indicating the necessity of a wider contextual positioning of cultural consumption and its perception in relation to other factors, thus showing that musical preferences can no longer be used as unmistakable indicators of social power relations, but that the cultural capital of those who are positioned higher on the social scale is reflected in the recognition and consumption of a wide range of genres and different cultural products. This understanding is complemented by the results of our exploratory research, which provide an overview of social and cultural factors that shape musical affinities and create certain perceptual frameworks regarding the trap genre. Research examines cultural and identity aspects of musical preferences among the student population in the Republic of Srpska, focusing on the phenomenon of trap music. The sample consists of 284 respondents (78.52% female students and 21.48% male students of the University of Banja Luka and the University of East Sarajevo). Through quantitative methodology, which included an online survey of the convenience sample, the goal was to uncover how dominant social narratives about trap music are reflected or challenged within the student community. Although the research has shortcomings (in terms of the non-representative sample and the necessity of using a local method), preliminary findings indicate that music preferences depend on a wider socio-cultural context, that the student population cannot be viewed homogeneously and that listening to trap music is part of a life stage (early youth). In addition, it is important to conclude that the audience of this genre separates reality from artistic expression, but also recognizes the dominant capitalist dimension of the music industry.